2007
DOI: 10.1186/1741-7007-5-28
|View full text |Cite
|
Sign up to set email alerts
|

A 100%-complete sequence reveals unusually simple genomic features in the hot-spring red alga Cyanidioschyzon merolae

Abstract: Background: All previously reported eukaryotic nuclear genome sequences have been incomplete, especially in highly repeated units and chromosomal ends. Because repetitive DNA is important for many aspects of biology, complete chromosomal structures are fundamental for understanding eukaryotic cells. Our earlier, nearly complete genome sequence of the hot-spring red alga Cyanidioschyzon merolae revealed several unique features, including just three ribosomal DNA copies, very few introns, and a small total numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
201
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 272 publications
(210 citation statements)
references
References 38 publications
(53 reference statements)
3
201
0
1
Order By: Relevance
“…C. merolae has an extremely simple cell structure and a minimally redundant small genome (11)(12)(13)(14), therefore this alga is considered to be a suitable model to study the origin and evolution of photosynthetic eukaryotes. It is also useful for studying the fundamental transcriptional network because it possesses a small number of TFs: Ͻ100 for the 16.5 Mb of the nuclear genome (13,14). Thus, identification of TFs and elucidation of the underlying mechanism for any given regulatory process should be far easier than in more complex higher plants.…”
mentioning
confidence: 99%
“…C. merolae has an extremely simple cell structure and a minimally redundant small genome (11)(12)(13)(14), therefore this alga is considered to be a suitable model to study the origin and evolution of photosynthetic eukaryotes. It is also useful for studying the fundamental transcriptional network because it possesses a small number of TFs: Ͻ100 for the 16.5 Mb of the nuclear genome (13,14). Thus, identification of TFs and elucidation of the underlying mechanism for any given regulatory process should be far easier than in more complex higher plants.…”
mentioning
confidence: 99%
“…After completion of both ODR and NDR, division of the plastid, mitochondrion, and nucleus occurs sequentially and is followed by cell division (7). The complete nucleotide sequences of the 3 genomes of C. merolae have been determined (8)(9)(10)(11), with the result that many tools are now available or are under development for genomics analysis. In this study, we have identified the chemical signal that coordinates ODR and NDR in C. merolae and have shown that this mechanism is also working in flowering plants.…”
mentioning
confidence: 99%
“…S2F). Dnm1 is one of only two dynamins (Dnm1 and Dnm2) encoded in the C. merolae genome (7,11). Dnm1 and Dnm2 are important components of the mitochondrion-dividing (MD) machinery (9,14,15) and plastiddividing (PD) machinery (16,17), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were analyzed by a peptide mass fingerprinting search using a MALDI-TOF-MS (AXIMA-TOF 2 ; Shimadzu), based on the FASTA file distributed by the C. merolae Genome Project (7,11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation